Reasons for Revelation Mentioned in “Tahdheeb Al-Linguistics” by Abu Mansur Al-Azhari (370 AH) in Compilation, Graduation and Study (Raparin Journal of Humanities (RJH), 2021)
This research deals with the discussion of an important aspect of the science of exegesis, which is the science of the causes of the revelation of the Qur’an, and with this science the exegete stands on the correct understanding of the meaning of the verse, especially that which was revealed for a reason, and it talks about a brief summary of the life of Abu Mansour Al-Azhari, the author of the book “Tahdheeb Al-Lugha”. And the definition of the aforementioned book, and the concept of the causes of revelation in terms of its definition in language and convention, and it reviews the benefits of the causes of revelation, its formula, the method of knowledge, and the controls of weighting between two different narrations regarding the cause of revelation of one verse. By graduating the reason based on the books written in this science, then the reason is from the books of hadith, and if it is not found in them, then relying on the interpretations ascribed to them, then studying the reason depends on the sayings of the commentators, and he mentions the result reached by the researcher for each reason, and the research is concluded with a conclusion in which the most important Results, and a list of the sources and references that he relied on.